The situated self - Ismael, Jenann, 1968- (Oxford : Oxford University Press, 2007)
This text focuses on the metaphysics and the philosophy of language and mind. It tackles a philosophical question whose origin goes back to Descartes: What am I? The self is not a mere thing among things - but if so, what is it, and what is its relationship to the world?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Self (Philosophy)